Cutaneous Emphysema and Craniocervical Bone Pneumatization - Turowski, Bernard; Rettig, Juergen; Raab, Peter; Zanella, Friedhelm E. (American Journal of Neuroradiology, 2001)
Summary: We report a case of pneumatization of the upper cervical spine and the craniocervical junction, including the occipital bone, accompanied by extensive soft tissue emphysema. There was no history of trauma or surgery. Follow-up X-ray and CT demonstrated the development of those changes. A combination of a developmental abnormality and the unusual habit of frequent Valsalva's maneuvers may have led to those findings. Clinical consequences will be discussed.